Clinical change in psychopathic traits after the PSYCHOPATHY.COMP program: preliminary findings of a controlled trial with male detained youth - Ribeiro Silva, Diana (Journal of experimental criminology, 2021)
To assess the preliminary efficacy of the PSYCHOPATHY.COMP in reducing psychopathic traits among male detained youth., In this controlled trial, a treatment group (n = 24) and a control group (n = 22) answered the Youth Psychopathic Traits Inventory-Short at baseline and post-treatment. Treatment participants attended the PSYCHOPATHY.COMP, in addition to the Treatment As Usual (TAU); controls only received TAU. The treatment effects were tested both at a group level (2 × 2 mixed ANOVA) and at an individual level (Reliable Change Index; RCI)., ANOVAs showed medium to large effect sizes (η2p), while RCIs revealed strong to moderate effect sizes (Cramer’s V)., Despite the limitations, this study offered preliminary evidence for the efficacy of the PSYCHOPATHY.COMP, suggesting that interventions targeting psychopathic traits should be considered in the rehabilitation of detained youth, as the absence of tailored interventions may increase the levels of psychopathic traits and its associated risks.